Integrated Metabolomics and Targeted Gene Transcription Analysis Reveal Global Bacterial Antimonite Resistance Mechanisms - Li, Jingxin; Zhang, Yuxiao; Wang, Xing; Walk, Seth T.; Wang, Gejiao (Frontiers in Microbiology, 2021)
Antimony (Sb) resistant bacteria have potential applications in the remediation of Sb contaminated sites. However, the effect of Sb(III) exposure on whole-cell metabolic change has not been studied. Herein, we combined untargeted metabolomics with a previous proteomics dataset and confirmatory gene transcription analysis to identify metabolic responses to Sb(III) exposure in Agrobacterium tumefaciens GW4. Dynamic changes in metabolism between control and Sb(III) exposed groups were clearly shown. KEGG pathway analysis suggested that with Sb(III) exposure: i) the branching pathway of gluconeogenesis is down-regulated, resulting in up-regulation of pentose phosphate pathway to provide precursors of anabolism and NADPH; ii) glycerophospholipid and arachidonic acid metabolisms are down-regulated, resulting in more acetyl-CoA entry into the TCA cycle and increased capacity to produce energy and macromolecular synthesis; iii) nucleotide and fatty acid synthesis pathways are all increased perhaps to protect cells from DNA and lipid peroxidation; iv) nicotinate metabolism increases which likely leads to increased production of co-enzymes (e.g. NAD+ and NADP+) for maintenance of cellular redox and Sb(III) oxidation. Expectedly, the total NADP+/NADPH content, total glutathione, and reduced glutathione contents were all increased after Sb(III) exposure in strain GW4, which contribute to maintaining the reduced state of the cytoplasm. Our results provide novel information regarding global bacterial responses to Sb(III) exposure from a single gene level to the entire metabolome and provide specific hypotheses regarding the metabolic change to be addressed in future research.